Economic Action and Social Structure: the Problem of Embeddedness - ГрановеттерМарк (Journal of Economic Sociology, 2010)
The paper deals with the problem of embeddedness of economic behavior in the social relations. This part of the text contains the theoretical definitions of embeddedness. The author analyzes over- and half-socialized concepts of human action in sociology and in economics. The issues of trust and fraud in economic life are in the focus.